Inmates' perspectives on prison drug treatment: A qualitative study from three prisons in Denmark. (June 2015) - Frank, Vibeke Asmussen; Dahl, Helle Vibeke; Holm, Karina Ellegaard; Kolind, Torsten
The purpose of this article is to employ a user-perspective on prison drug treatment. Based on data from 32 in-depth qualitative interviews with inmates and three months of observational studies in three Danish prisons, the article examines how drug treatment in prison is experienced and strategically approached by enrolled inmates. The analysis shows the broad range of reasons for entering as well as staying in treatment during imprisonment, including how the prison setting influences and constrains inmates' experiences in different ways. By employing a user-perspective the article follows the research tradition, beginning in the 1990s, of including drug users' perspectives on treatment. It adds important information to the drug treatment literature on issues such as organization, social relations and output of drug treatment. Including a user-perspective, we were able to uncover aspects and experiences of treatment services that differ from other actors in the field, e.g. counsellors, medical doctors, nurses, politicians, and officers. A user-perspective also challenges our understanding of what is at play in drug treatment as well as treatment in prisons.